A womb and a tomb: mothers’ experiences of single fetal loss in a twin pregnancy - Avital Gershfeld-Litvin; Nathalie Yael Nur (BMC Pregnancy and Childbirth)
Abstract Background Twin pregnancies carry a higher risk of complications and negative outcomes compared to single fetal pregnancies. The incidence of twin pregnancies has increased over the last three decades due to the use of assisted reproduction technologies and advancing maternal age. While extensive research exists regarding the experiences of women following perinatal loss, research on the experiences of women following single fetal loss in a twin pregnancy is very limited. The purpose of this study was to explore the experiences of women who endured the loss of a single twin in a twin pregnancy. Methods Semi-structured interviews were conducted with 12 Israeli women whose losses had taken place between six months and 11 years prior to their enrollment in the study. Interviews were analyzed using thematic analysis. Results Four themes were generated: (1) in the beginning there was joy; (2) a period of tremendous darkness; (3) then they took him away; and (4) the main thing is that you have a living child. Conclusions Addressing both individual and societal aspects of this grief may foster better support for mothers in their dual roles as parents and mourners. Further research is needed to generalize these findings to a wider population and to deepen our understanding of grief experiences among women following twin pregnancies.